Thermo-Fluid Analysis on the Efficiency of Wet Compression Process - P. V. Hudson Dharmaraj; T. H. Kim; A. Suryan; H. D. Kim (Journal of Applied Fluid Mechanics, 2022)
Wet compression has been well known as a promising technology to effectively increase the power output of the gas turbine engine by introducing fine droplets of water into the compressor stages. This lessens the temperature rise throughout the compression process of gas, thus leading to the reduction in the compressor work. A considerable amount of research on the wet compression process has been performed to date, but the detailed compression process of the two-phase gas media and fine droplets is not well understood yet. In the present study, the thermo-fluid analysis has been done on a simple flow model that has a spherical droplet of water inside a cylinder-piston system. The model is validated by using a quasi-steady D2 – Law of evaporation model. The compression rate is varied by employing the piston movement under various flow conditions such as percentage of overspray, water droplet diameter, relative humidity, and temperature. The results obtained show that for a higher percentage of overspray, smaller droplet diameters and a slower compression rate the efficiency obtained is high. Which results in lesser compressor work. The effects of compression rate, droplet diameter, overspray, and the efficiency of the wet compression have been explained and analyzed in detail.